INTEGRASI NILAI RAHMAH DALAM KONSELING HUMANISTIK SEBAGAI PENDEKATAN INTERVENSI KECEMASAN PSIKOLOGIS GENERASI Z DI SMA N 1 SRAGI - Muhammad Nur Ilham; Ziyadah El Fadllilah; Finta Nur Febriana; Fauzi, Nadzifah A'isyah; Rahmi Anekasari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Psychological anxiety among Generation Z has become a growing concern in educational settings due to increasing academic demands, social pressures, and the challenges of modern life. This study aimed to examine the dynamics of psychological anxiety experienced by Generation Z students at SMA Negeri 1 Sragi, formulate the concept of integrating rahmah values into humanistic counseling as an intervention approach, describe its implementation in school counseling services, and analyze its implications for addressing students’ psychological anxiety. This research employed a qualitative case study approach. Data were collected through interviews, observations, and documentation involving students and guidance and counseling teachers. The data were analyzed through data reduction, data presentation, and conclusion drawing. The findings revealed that academic anxiety was the most dominant form of anxiety experienced by students, particularly related to academic achievement, examination results, and expectations for higher education. Other contributing factors included limited supportive communication within families, social comparison with peers, and stigma toward counseling services. The integration of rahmah values into humanistic counseling was conceptualized through four core dimensions: empathy, unconditional positive regard, self-awareness development (muhasabah), and compassion-based emotional support. The implementation of these values was reflected in counseling relationships characterized by empathy, acceptance, confidentiality, and respect for students’ dignity. Students reported feeling more comfortable, understood, and accepted during counseling sessions, which encouraged greater self-disclosure and trust in counselors. Furthermore, the integration of rahmah values contributed positively to students’ ability to manage anxiety, enhance self-confidence, and develop adaptive coping strategies. The study concludes that integrating rahmah values into humanistic counseling represents an effective and holistic approach to promoting the mental health and psychological well-being of Generation Z students in school environments.